Time required to change yearling steers from roughage to high grain ration; using Stilbestrol as an implant and in the feed; worming yearling steers - Hall, M.C.; Smith, E.F.; Nelson, S. (Kansas Agricultural Experiment Station, 2011)
Sixty yearling steers were removed from bluestem pasture October29, 1965 and trucked six miles to the KSU beef cattle research barn where they received prairie hay and had access to a self-feeder of 50% bran and 50% dry rolled sorghum grain. October 30 they were weighed and divided into three lots of 20 steers.
Keywords: Beef; Roughage; Implants